Les unités pastorales du Sahel sénégalais, outils de gestion de l’élevage et des espaces pastoraux - Abdrahmane Wane; Véronique Ancey; Basile Grosdidier (Développement Durable et Territoires)
In Ferlo (Senegalese Sahel), the sustainability of the livestock farming depends on the diversity and the flexibility of the regulations of mobility. Since the 90s, the PAPEL (Senegalese Support Project for Livestock) has intervened in the area in order to manage the natural resources on the scale of the pastoral units (UP) with the declared objective to ensure the control and the sustainability of this activity. We tried to estimate the relevance of the general implementation of this large-scale project by the yardstick of the characteristics peculiar to Pastoralism, henceforth known as the best valorisation form in the uncertain environment of Ferlo. Even if the pastoral units as tools of the natural resource management have demonstrated their interest in many cases of the first stage of the project in the pastoral area, it seems that, in the present Senegalese context of the agricultural and land sectoral policy of private monopolizing of resources, the systematic general implementation of the pattern of pastoral units throughout the whole country would be likely to threaten the sustainability of the pastoral mobility.